2009
DOI: 10.4238/vol8-1gmr538
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of natural populations of Anemopaegma arvense (Bignoniaceae) in the Cerrado of São Paulo State, Brazil

Abstract: ABSTrACT. Catuaba (Anemopaegma arvense), a Bignoniaceae species endemic to Cerrado regions, shows anticancer properties and is widely used as a stimulant in traditional medicine. We evaluated the genetic diversity of seven populations found in the State of São Paulo, using random amplified polymorphic DNA markers. After optimization of the amplification reaction, 10 selected primers produced 70 reproducible bands, with 72.8% polymorphism. The greatest genetic diversity was observed within populations (71.72%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This hazardous fate of the sexual embryo in E. pubescens would explain the low genetic variability and a mostly clonal population found in this species (Martins & Oliveira, ). In A. arvense , genetic variability is greater within populations than between them (Batistini et al ., ) and this is probably attributable to the greater survival of viable sexual embryos, as described for other polyembryonic species (Batygina, 1999a, b; Batygina & Vinogradova, ; Hörandl & Paun, ).…”
Section: Discussionmentioning
confidence: 82%
“…This hazardous fate of the sexual embryo in E. pubescens would explain the low genetic variability and a mostly clonal population found in this species (Martins & Oliveira, ). In A. arvense , genetic variability is greater within populations than between them (Batistini et al ., ) and this is probably attributable to the greater survival of viable sexual embryos, as described for other polyembryonic species (Batygina, 1999a, b; Batygina & Vinogradova, ; Hörandl & Paun, ).…”
Section: Discussionmentioning
confidence: 82%
“…Other populations of native species from Brazilian savanna have been characterized with high level of genetic differentiation among them, e.g ., C. brasiliense ( F ST = 0.260) , Eugenia dysenterica ( F ST = 0.270) , D. alata , H. stigonocarpa ( F ST = 0.692), Jacaranda decurrens ( F ST = 0.263) , S. adstringens ( F ST = 0.290) , and A. arvense ( F ST = 0.283) . This genetic divergence found between populations of A. crassiflora and other species of Cerrado may possibly reflects the isolation between populations due to the processes of fragmentation and the reduction in size of the population.…”
Section: Resultsmentioning
confidence: 92%
“…In the past 40 years, extensive agricultural practices have caused changes in up to 60% of this ecosystem . For several authors, this fragmentation represents a huge barrier that hinders the gene exchange between populations, which might explain the high level of genetic differentiation among them . Loveless and Hamrick suggested that species characterized by entomophily are more sensitive to fragmented ecosystems due limited pollen movement, which can accentuate the differentiation among populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The θ B value was determined under four models for dominant markers: Free model (Free f ), estimating inbreeding values; model θ B = 0 and model f = 0, where θ B and f were respectively fixed at zero; and Full model, encompassing all previous possibilities. Simulations were conducted using the Markov Monte Carlo chain (MCMC) [ 44 ]. The model selection was based on the observation of DIC (Deviance Information Criterion) values, adopting the one with the lowest DIC value [ 45 ].…”
Section: Methodsmentioning
confidence: 99%